2002
DOI: 10.1080/089106002760003279
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Selection and Characteristics of Lactobacillus paracasei subsp. paracasei F19

Abstract: Lactobacillus strains were isolated from the deep colonic mucus layer of patients without gastrointestinal disease and screened for binding of porcine mucin. Strains exerting high mucin binding were further characterized as to survival ability in the gastrointestinal tract, viz pH stability and bile tolerance. Lactobacillus F19, identi ed as Lactobacillus paracasei ssp paracasei, bound gastric and bovine mucin, collagen I and III and bronectin (Fn), and expressed high surface hydrophobicity. It survived exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 15 publications
0
24
0
2
Order By: Relevance
“…Some lactobacilli produce antioxidant factors also in the human gastrointestinal tract (Ljungh et al 2002). The majority of milk bacteria show antioxidant behavior (eliminating the excess oxygen free radicals) producing superoxide dismutase, or glutathione.…”
Section: Antioxidant Effectsmentioning
confidence: 99%
“…Some lactobacilli produce antioxidant factors also in the human gastrointestinal tract (Ljungh et al 2002). The majority of milk bacteria show antioxidant behavior (eliminating the excess oxygen free radicals) producing superoxide dismutase, or glutathione.…”
Section: Antioxidant Effectsmentioning
confidence: 99%
“…Recent experimental studies could demonstrate a synergistic effect if several probiotic strains were combined [21]. A University of Lund based microbiology team performed an extensive screening of the human gut and isolated 355 various strains of lactic acid bacteria [22]. The ability of these strains to bind to porcine mucin, to express cell surface hydrophobicity, and to bind to collagen, fibronectin, and other extracellular matrix proteins were extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical study, Songisepp et al [65] reported that the healthy volunteers consumed 150 g of goat milk fermented with a starter culture Lactobacillus fermentum ME-3 for 21 days had shown important improvement of the overall antioxidant activity of blood, as well as antioxidant status, prolonged resistance of lipoprotein fraction to oxidation, reduced level of peroxide lipoproteins and oxidized LDL cholesterol, reduced level of glutathione redox ratio, and increased overall antioxidant activity. Moreover, some lactobacilli were reported to produce antioxidant factors in the human gastrointestinal tract [66]. Kullisaar et al [67] had identified two Lactobacillus fermentum strains (E-3 and E-18) with antioxidative properties that overcome exo-and endogenous oxidative stress.…”
Section: Discussionmentioning
confidence: 99%